Hollow cylinder sample test using a dynamic mechanical analyser - Noparatanakailas V; Seadan M (Journal of Rubber Research, 2000)
A hollow cylinder specimen was designed for testing rubber in shear deformation using a Dynamic Mechanical Analyser series 7. Test results showed that a lower coefficient of variation for storage modulus is obtained with this system than using a compressive pellet sample ia a cup-and-plate deformation. This shear test has been developed to characterise four grades of natural rubber: Standard Thai Rubber (STR) 5 L; STR 20; RSS and skim block. Over a frequency range of 0.1Hz to 50.0Hz and 0.5;strain, the effect of rubber grade, temperature, degree of mastication and the amount of carbon black (N330) was investigated. Dynamic complex and real viscocities were determined and showed good agreement with the shear flow viscosity obtained from experiments with a Rosand capillary rheometer. However, limitations of this shear technique were found, such as a failure of test specimen at temperatures approaching the molten state of rubber, and insufficient force control for very stiff specimens with high carbon black loading.
Keywords: Hollow cylinder